INTEGRASI KUALITAS SUMBER DAYA MANUSIA, SERTIFIKASI HALAL DAN DIGITALISASI SEBAGAI PENDORONG KINERJA BERKELANJUTAN UMKM - Desnita Dwireni; Ach. Yasin (Jurnal Ilmiah Ekonomi Islam, 2026)
The implementation of sustainable performance has become essential for businesses that integrate economic, social, and environmental aspects. This condition requires business actors to balance profit growth with social responsibility and environmental preservation to ensure long-term business sustainability. This study aims to analyze the factors influencing the sustainable performance of Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Kediri City. The method used is a quantitative approach with primary data obtained through the distribution of questionnaires. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM The results indicate that Human Resource Quality, Halal Certification, and Perceived Ease of Use have a significant effect on Sustainable Performance. Meanwhile, Perceived Usefulness does not have a significant impact on Sustainable Performance. Therefore, MSMEs actors need to strengthen their competencies, optimize halal production standards, and utilize digital technology as key strategies to support the implementation of sustainable performance.